2013
DOI: 10.1111/and.12209
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil, contained in eicosapentaenoic acid and docosahexaenoic acid, attenuates testicular and spermatological damage induced by cisplatin in rats

Abstract: The aim of this study was to investigate the beneficial effects of the fish oil (FO) supplementation on oxidative stress, sperm characteristics and histological alterations in the male reproductive system of rats against cisplatin (CP) toxicity. The rats were divided randomly into 4 equal groups (control, FO, CP and FO + CP). FO was orally administered at the dose of 1 softgel per rat per day for 14 days and CP was intraperitoneally given at the dose of 7 mg kg(-1) with a single injection. In CP + FO group, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…AB means ATRA combined with BDMC Aydin, Kaya, & Oguz, 2014;Ilbey et al, 2009;Tuglu et al, 2015). Hep3B cells (2 × 10 5 cells/well) were treated with 50 μM of ATRA or with 15 μM of BDMC or their combination for 48 hr.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…AB means ATRA combined with BDMC Aydin, Kaya, & Oguz, 2014;Ilbey et al, 2009;Tuglu et al, 2015). Hep3B cells (2 × 10 5 cells/well) were treated with 50 μM of ATRA or with 15 μM of BDMC or their combination for 48 hr.…”
Section: F I G U R Ementioning
confidence: 99%
“…# p < .05 was significant difference compared with ATRA only or BDMC only group. AB means ATRA combined with BDMC Aydin, Kaya, & Oguz, 2014;Ilbey et al, 2009;Tuglu et al, 2015).…”
Section: F I G U R Ementioning
confidence: 99%
“…The high polyunsaturated membrane lipid content of the testes makes the testes more susceptible to the effects of oxidative agents such as CP (Gevrek & Erdemir, ). The protective effect of various natural substances, including fish oil (Ciftci et al, ), curcumin (Gevrek & Erdemir, ), resveratrol (Reddy et al, ), hesperidin (Kaya et al, ) and rutin (Aksu et al, ), against CP‐induced reproductive system damage has also been demonstrated in many studies. To our knowledge, the potential beneficial effects of β‐glucans against CP‐induced reproductive toxicity have not been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin (CP) is a chemotherapeutic agent that widely used for many different types of cancer, such as lung, stomach, ovarian and testicular (Ciftci, Cetin, Aydin, Kaya, & Oguz, ; Kaya, Ciftci, Cetin, Doğan, & Başak, ). The clinical usage of CP is restricted due to its severe dose‐dependent side effects (Bayindir et al, ; Eid, Abdelkader, Abd El‐Raouf, Fawzy, & El‐Denshary, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation